2006
DOI: 10.1523/jneurosci.4573-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Protein Synthesis and Degradation in Long-Term Potentiation of Schaffer Collateral CA1 Synapses

Abstract: Expression of synaptic plasticity involves the translation of mRNA into protein and, probably, active protein degradation via the proteasome pathway. Here, we report on the rapid activation of synthesis and degradation of a probe protein with the induction of long-term potentiation (LTP) in the hippocampal Schaffer collateral CA1 pathway. The proteasome inhibitor MG132 significantly reduced the field EPSP slope potentiation and LTP maintenance without acutely affecting basal synaptic transmission. To visualize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 61 publications
8
111
0
Order By: Relevance
“…Although the dynamics of Arc turnover remains to be directly studied, rapid turnover of Arc (on the order of minutes to hours) has been reported in several in vitro studies (Yin et al, 2002;Rao et al, 2006). Interestingly, two recent studies showed that drugs that block proteosome-dependent degradation of proteins, such as protein synthesis inhibitors, prevent formation of stable LTP (Fonseca et al, 2006;Karpova et al, 2006). This surprising observation suggested that stable LTP involves simultaneous rapid synthesis and degradation of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although the dynamics of Arc turnover remains to be directly studied, rapid turnover of Arc (on the order of minutes to hours) has been reported in several in vitro studies (Yin et al, 2002;Rao et al, 2006). Interestingly, two recent studies showed that drugs that block proteosome-dependent degradation of proteins, such as protein synthesis inhibitors, prevent formation of stable LTP (Fonseca et al, 2006;Karpova et al, 2006). This surprising observation suggested that stable LTP involves simultaneous rapid synthesis and degradation of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Additional investigation into the expression patterns of the Thy1-Usp14LF transgene should provide important insights into the dysfunctional neuronal circuit or circuits in the ax J mice. It is becoming increasingly clear that changes in the activity of the UPS play an important role in both synaptic plasticity and disease (Wilson et al, 2002;Speese et al, 2003;Yi and Ehlers, 2005;Karpova et al, 2006;Patrick, 2006). It is therefore possible that Usp14 has evolved a specialized function in neurons to regulate the ubiquitin side chain length of proteins bound to the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitoylation of PSD-95 favors its synaptic localization (ElHusseini Ael et al 2002). Activity-dependent degradation of synaptic proteins-which is required for LTP and LTD, as well as learning and memory (Colledge et al 2003;Fonseca et al 2006;Karpova et al 2006;Lee et al 2008)-may be aided by the rapid redistribution of proteasomes to postsynaptic sites following synaptic stimulation (Bingol and Schuman 2006;Bingol et al 2010).…”
Section: Basal and Activity-dependent Protein Turnover In The Psdmentioning
confidence: 99%